“Efecto de la bioestimulación mediante inyección en plantas cosechadas de banano (Musa paradisiaca sp.) para el mejoramiento fenológico del hijo”. - Chávez Jácome, Patricio Javier (2023)
The cultivation of bananas (Musa paradisiaca) is the main agricultural export product of Ecuador, which generates foreign exchange and jobs in rural and urban areas, and is the main source of the Ecuadorian economy, mainly in the provinces of Guayas, El Oro, Los Ríos and the subtropics of Cotopaxi, being the support for the livelihood of these Ecuadorian families in the country. With the objective of evaluating the effect of biostimulation by injection in banana harvest plants (musa paradisiaca sp.). The investigation lasted ninety days in the field, the trial used in the investigation had a completely randomized design. The following variables were evaluated: plant height, stem circumference, leaf length and width, leaf emission, growth rate, leaf area and economic analysis by treatment. Where three plants with different treatments were evaluated. The results shown by the research is that brassinosteroids obtained the best results in the variables evaluated for plant height, total number of leaves, leaf length, best growth rate and leaf area. The lowest costs per hectare were in humic acids where a greater benefit is obtained with a value of 17.50 usd, since it also favors the vegetative characteristics of the plants.